Pengaruh Karakteristik Individu, Karakteristik Pekerjaan, Iklim Organisasi terhadap Kepuasan dan Kinerja Karyawan - Lubis, Yusniar (Jurnal Trikonomika, 2012)
The analysis of Employee Characteristic as Individual and Job Characteristic on Job Satisfaction. The object of this research was employees of PTPN III and PTPN IV North Sumatra. This research used descriptive and verification method. Proportional Random Sampling was used as sampling technique with sample of 270 participants. The results of this research showed that 1) the condition and implementation of employees characteristic as individual as well as job characteristic on job satisfaction could be categorized good. 2) individual characteristic influence on job satisfaction. 3) job characteristic influence on job satisfaction. 4) organization climate influence on job satisfaction. 5) individual characteristic, job characteristic, organization climate simultanously influence on job satisfaction. 6) job satisfaction influence on employee performance.